Requisitos dinâmicos de controle para o estágio de conversão C.C.-C.C. aplicado em sistemas fotovoltaicos - Figueira, Henrique Horst (2020)
Photovoltaic systems (PVs), in their usual condition, are controlled to track the maximum power point (MPP) in a natural solar dynamic. However, with the cheapness of solar energy and its integration with the most diverse areas of cities, the PV system will increasingly be subjected to solar dynamics with multiple changes, such as, for example, the integration of PV systems on solar highways. Such dynamics, resulting from vehicle shading, cause extra effort for static converters designed to search for PMP. In this scenario, this work addresses the study of the speed of natural solar dynamics and with multiple changes applied to PV systems, develops metrics for comparative performance evaluation of the global efficiency of the maximum power point tracker (MPPT) applied to natural solar dynamics, verifies the need for fast cascade control for a dual-stage converter for application in natural solar dynamics and with multiple changes, and contributes to the improvement of cascade control techniques for dual-stage PV systems based on virtual resistance, where the control law consists of an internal current loop and an external voltage loop.